Reversible Wenckebach Phenomenon in a Young Patient with Dengue Fever: A Case Report - Subash Mohan Thulasi; Yohidha Balamurugan; Sornavalli Valliappan; Visvesvaran Salitteeswaran; PK Ananthakumar (Journal of Clinical and Diagnostic Research)
Dengue fever, caused by the Dengue Virus (DENV) of the Flaviviridae family, is widespread in tropical and subtropical regions, with India experiencing a high burden of disease. Although many cases remain asymptomatic or mild, severe complications, including cardiac manifestations, can occur. This article reports uncommon presentation of dengue-associated transient conduction disturbances without overt myocardial injury. A previously healthy 22-year-old male presented with intermittent fever, chills, generalised myalgia, gastrointestinal symptoms and dehydration for five days. Initial evaluation at a local clinic revealed thrombocytopenia and a normal Electrocardiogram (ECG). On hospital admission, the patient exhibited dehydration, bleeding manifestations (oral mucosal and gingival haemorrhages), and an irregular pulse. Laboratory tests indicated thrombocytopenia, transaminitis, and pre-renal acute kidney injury, while dengue NS1 antigen and IgM antibodies were positive. A 12-lead ECG performed on admission revealed a second-degree Mobitz Type I (Wenckebach) atrioventricular block, which was confirmed by 24-hour Holter monitoring. Cardiac enzymes were within normal limits, and echocardiography showed preserved left ventricular function without evidence of myocarditis. Management included intravenous hydration and platelet transfusions. Serial ECG monitoring demonstrated resolution of the Atrio-ventricular (AV) block by day 4 of hospitalisation, and the patient’s renal and hepatic functions normalised, leading to discharge on day 7. This case underscores the need for diligent cardiac monitoring in dengue fever, as transient conduction disturbances may occur even without significant myocardial involvement. Transient low-degree AV block in dengue fever, although seemingly benign, may herald severe cardiac complications. Prompt recognition and supportive management are pivotal in mitigating potential cardiac complications.